2019
DOI: 10.1186/s12889-019-7211-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of diagnosed and undiagnosed hypertension in the indigenous Kuna population of Panamá

Abstract: Background To determine the prevalence of hypertension and investigate sociodemographic correlates in an indigenous Kuna community living on the San Blas islands of Panama. Methods Data was collected from adults using a paper-based survey using a cross sectional study design. Blood pressure was measured, and hypertension defined at two cut-points: 130/80 mmHg and 140/90 mmHg. Individuals with undiagnosed hypertension had a blood pressure measurement that indicated hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…A higher prevalence of HTN, diagnosed or undiagnosed, among men was also reported by Hanna et al in Panama. 29 These gender differences in HTN prevalence are due to both biological and behavioral factors. 30 Biological factors include sex hormones, chromosomal differences, and other biological gender differences that are protective against HTN.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of HTN, diagnosed or undiagnosed, among men was also reported by Hanna et al in Panama. 29 These gender differences in HTN prevalence are due to both biological and behavioral factors. 30 Biological factors include sex hormones, chromosomal differences, and other biological gender differences that are protective against HTN.…”
Section: Discussionmentioning
confidence: 99%
“…Aside obesity, hypertension has been a major public health concern due to its adverse health events. Several studies have shown that most commercial workers are unaware of their elevated blood pressure and as such suffer from chronic undiagnosed hypertension [41,42]. Early recognition and identification of early risk of cardiovascular risk factors such as hypertension at the suboptimal health phase [43] will inform the decision for predictive, preventive and personalized medicine [44].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive heart disease is a long-term condition that worsens with time. Several risk factors, including advancing age, family history, obesity, high salt diets (more than 3 g per day), physical inactivity, and excessive alcohol intake, have strong and independent connections with the onset of hypertension (5)(6)(7). In Bangladesh, roughly 68% of deaths are caused by noncommunicable diseases, with hypertension accounting for 15-20 % (8).…”
Section: Introductionmentioning
confidence: 99%